Wojna kulturowa między Rosją a Ukrainą. Sposób na osłabienie rosyjskiego kulturowego imperializmu (Politeja, 2022)
CULTURAL WAR BETWEEN RUSSIA AND UKRAINE: A WAY TO WEAKEN RUSSIAN CULTURAL IMPERIALISMThe imperial plans of the Russian Federation towards Ukraine at the end of February 2022 passed to the next stage and took the form of a full-scale war, which covers not only the military, political, economic, but also cultural spheres. The author of this article, starting from this assumption, presents an analysis of the war between Russia and Ukraine from the cultural and anthropological perspective. He refers to the so-called the phenomenon of the “small-Russian nature” of the Ukrainian nation, which, starting from the times of the Russian Empire, influenced the perception of Ukrainians as being secondary to Russians. This situation didn’t change even after Ukraine regained its independence in 1991. Only the events on the Maidan in Kiev, the annexation of Crimea and the invasion of Donbas caused a change in cultural vectors. Ukraine began to forge its own national cultural identity, completely breaking away from what was Russian. The full-scale war, unleashed at the end of February, significantly sharpened this rhetoric, additionally underpinned by the policy of cultural sanctions applied by the West. Therefore, the aim of this article is to present the Russian-Ukrainian cultural war, the consequence of which is the process of shaping an independent Ukrainian cultural awareness.